Impact of an opioid risk reduction initiative on motor vehicle crash risk among chronic opioid therapy patients. Issue 1 (14th November 2016) - Hansen, Ryan N.; Walker, Rod L.; Shortreed, Susan M.; Dublin, Sascha; Saunders, Kathleen; Ludman, Evette J.; Von Korff, Michael
Abstract: Purpose: Although prescription opioids have been associated with higher motor vehicle crash (MVC) risk, it is unknown whether health system initiatives to better manage chronic opioid therapy (COT) can reduce MVC risk at the population level. Methods: We conducted an interrupted time series population‐level cohort study at Group Health (GH), between January 2006 and September 2014, comparing MVC risk among COT patients who were GH members receiving care in either group practice or contracted care settings. Group practice COT risk reduction initiatives were implemented in two phases: (1) altered prescribing expectations and (2) multifaceted initiatives. These initiatives did not exist in the contracted care network. We compared the adjusted quarterly rate of MVC between group practice and contracted care patients over time using a modified Poisson regression model for a binary outcome. Results: A total of 32 691 COT patients (27.4% from contracted care) met eligibility criteria and experienced a total of 1956 MVCs during study follow‐up (mean, 8.1 quarters per person), of which 810 were serious injury crashes. Crash rates were not significantly different between the patient groups within any of the time periods. Analyses stratified by concurrent prescription of a sedative hypnotic or benzodiazepine found no significant difference between the group practice and contracted care patients. There was a modest elevation of MVC risk for high‐dose patients relative to former COT patients who stopped receiving opioids. Conclusions: The risk of MVC was not mitigated in a large cohort of COT patients exposed to a health plan policy initiative that substantially lowered mean opioid dose. Copyright © 2016 John Wiley & Sons, Ltd.